Oxidative impact on lipoprotein structure: Insights from dynamic light scattering - Nickolette Kong; Natalia Penaloza; Gustavo Agreda; Angela B. Nguyen; Joseph Gutheinz; Alison Tran; Nhi Nguyen; Tuong Vi Ho; Ana Marin; Birgit Mellis; Richa Chandra (Biochemistry and Biophysics Reports)
Cardiovascular disease (CVD) is the number one cause of mortality worldwide, with oxidative stress contributing significantly to its pathogenesis. Lipoproteins, key biomolecules in lipid transport, are particularly susceptible to oxidative modifications, which can contribute to atherogenesis. The need for advanced analytical tools to better understand the pathogenesis of cardiovascular disease (CVD) is critical due to its significant impact on public health. Clinicians often rely on indirect calculations of low-density lipoprotein (LDL) as a primary diagnostic indicator, which can oversimplify and overlook the complex changes in lipoprotein structure and function and therefore the complex etiology of CVD. Here it is demonstrated that dynamic light scattering (DLS) is sensitive and effective at measuring variation in lipoprotein size distributions following oxidative damage caused by peroxidation and nitration—two common physiological processes that play dual roles in both normal and pathogenic states. We establish the utility of DLS in detecting subtle variations in lipoprotein size, including potential aggregation and fission events resulting from chemical modifications. Our work highlights the value of DLS in advancing our understanding of the pathogenic mechanisms underlying CVD development, while also providing a foundational framework to study other biological processes and their effects on lipoproteins, ultimately guiding the development of therapies to address these harmful processes.